(untitled) (Journal of Medical & Health Sciences Review, 2025)
The current study aimed to assess the impact of extender supplementation of a combination of three fatty acids (arachidic acid 20 ng/mL, α-linolenic acid 5.0 ng/mL and cholesterol 5.0 ng/mL) for cryopreservation of buffalo sperm. Three adult buffalo bulls of the same age were used to collect semen using an artificial vagina (42°C). Tris citric acid extender (37°C) was used to dilute qualified semen ejaculates (>0.5 billion per mL conc., >1 mL volume, >60% motility). Six different experimental extenders were prepared containing fatty acids (arachidic acid 20 ng/mL, α-linolenic acid 5.0 ng/mL and cholesterol 5.0 ng/mL) alone and in combinations. The control extender was without any fatty acid supplementation. Extended semen chilled to 4°C (in 2 hours) was placed for equilibration (at 4°C) for 4 hours. Plastic straws 0.5 mL (4°C) were used to fill the equilibrated semen. Liquid nitrogen gas vapours were used to further freeze the semen for 10 min. and then dipped in liquid-nitrogen for storing. After 24 hours thawing was done (37°C) for 30 seconds and semen quality was assessed. Supplementation of combination of fatty acids in extender didn’t improved percentage of progressive sperm motility, plasma membrane intactness, viable sperm and intact chromatin of cryopreserved buffalo semen compared to supplementation of fatty acids alone in extender and control. In conclusiothe n, addition of fatty acids in combination to a semen extender was not found beneficial to improve quality of cryopreserved buffalo semen.